Functional analysis reveals ionotropic GABA receptor subunit RDL is a target site of ivermectin and fluralaner in the yellow fever mosquito, Aedes aegypti. Issue 10 (5th July 2022) - Wang, Qiuhui; Wang, Haocheng; Zhang, Yingxin; Chen, Jing; Upadhyay, Archana; Bhowmick, Biswajit; Hang, Jiayu; Wu, Shaoying; Liao, Chenghong; Han, Qian
Abstract: BACKGROUND: Ionotropic γ‐aminobutyric acid (iGABA) receptors are involved in various physiological activities in insects, including sleep, olfactory memory, movement, and resistance to viruses. Ivermectin and fluralaner can disturb the insect nervous system by binding to iGABA receptors, and are therefore an effective means for controlling insect pests. However, the molecular mechanisms underlying the insecticidal effect of both the compounds on Aedes. aegypti remain unexplored. RESULTS: In this study, we investigated the spatiotemporal expression profile of Ae. aegypti RDL ( Ae‐RDL ), a subunit of iGABA receptor. RDL dsRNA suppressed the expression of Ae‐RDL mRNA in Ae. aegypti larvae and adult by 60% and 50.67%,  resepectly. However, the physiology of Ae. aegypti larvae was not significantly affected. The mortality of Ae. aegypti larvae and adult females subjected to Ae‐RDL knockdown significantly decreased after exposure to ivermectin and fluralaner. Additionally, Ae‐RDL was cloned into Xenopus laevis oocytes and characterized using the two‐electrode voltage‐clamp method. The inward current was induced by GABA binding to the functional Ae‐RDL homomeric receptors at a median effective concentration (EC50 ) of 100.4 ± 59.95 μM (n > 3). The significant inhibitory effect of ivermectin and fluralaner on inward current indicated that both insecticides exerted a significant antagonistic effect on Ae‐RDL . However, ivermectin also showed strong agonistic as well as weak activation effects on Ae‐RDL . These contrasting effects of ivermectin on Ae‐RDL depended on ivermectin concentration. CONCLUSION: Our study revealed that Ae‐RDL subunit is a target of ivermectin and fluralaner, providing new insights into the insecticidal mechanism of both compounds in Ae. aegypti. © 2022 Society of Chemical Industry. Abstract : We verified the target relationship between Aedes aegypti iGABA receptor RDL subunit and ivermectin as well as fluralaner by RNAi and electrophysiological assay. It is also tested that the two insecticides kill Ae. aegypti larvae and adult by changing the open ways of iGABA receptor ion channels.